Frequency of Campylobacter spp in BARF food for dogs marketed in Lima, Peru - Saldaña Martinez, Kiara (2022)
The aim of this study was to determine the frequency of Campylobacter spp in biologically appropriate raw food (BARF) for dogs that are marketed in Lima, Peru. One hundred random samples of BARF food were collected from 10 commercial brands. Samples were collected from different batches. The horizontal method for the detection and enumeration of Campylobacter spp (ISO 10272-1:2017) was performed. Bolton Broth was used as enrichment medium and a CCDA selective medium, followed by a second Karmali selective medium for Campylobacter. Suspicious colonies were reseeded on Blood Agar. Campylobacter spp strains were isolated in 5 + 4.2% (5/100) of the samples.